Identification and Characterization of Chalcone Isomerase Genes Involved in Flavonoid Production in Dracaena cambodiana - Zhu, Jiahong; Zhao, Wan; Li, Rongshuang; Guo, Dong; Li, Huiliang; Wang, Ying; Mei, Wenli; Peng, Shiqing (Frontiers in Plant Science, 2021)
Chalcone isomerase (CHI) is the second key enzyme in the flavonoid biosynthesis pathway that catalyzes the isomerization of chalcones to flavanones. However, CHI family genes are not well understood in Dracaena cambodiana Pierre ex Gagnep, an important medicinal plant rich in flavonoids. In this study, 11 CHI family genes were identified from D. cambodiana, and they were classified into three types. Evolutionary and transcriptional profiling analysis revealed that DcCHI1 and DcCHI4 might be involved in flavonoid production. Both DcCHI1 and DcCHI4 displayed low expression levels in stem under normal growth conditions and were induced by methyle jasmonate (MeJA), 6-benzyl aminopurine (6-BA, synthetic cytokinin), ultraviolet-B (UV-B) and wounding. The recombinant proteins DcCHI1 and DcCHI4 were expressed in Escherichia coli and purified by His-Bind resin chromatography. Enzyme activity assay indicated that DcCHI1 catalyzed the formation of naringenin from naringenin chalcone, while DcCHI4 lacked this catalytic activity. Overexpression DcCHI1 or DcCHI4 enhanced the flavonoid production in D. cambodiana and tobacco. These findings implied that DcCHI1 and DcCHI4 play important roles in flavonoid production. Thus, our study will contribute to better understand the function and molecular mechanism of CHI family genes in the regulation of flavonoid production in D. cambodiana.